A Survey on Various Online Transaction, E-Commerce Security and Applications - Jotwani, Varsha; Dutta, Amit (International Journal of Computer Sciences and Engineering, 2025)
While the usage of ecommerce application, information and communication technology enhances in private and professional existence, personal data is extensively stored. While service providers require relying on recognizing their consumers, aware characteristics administration and privacy increases into a new assessment for the service user, particularly in the electronic service circumstance. At this time, recent technology infrastructures can support in on condition that security to both sides by assuring identification and privacy at the same time.